1976
DOI: 10.1002/1097-0142(197609)38:3<1344::aid-cncr2820380338>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Urinary polyamine levels in patients with localized malignancy

Abstract: Polyamine levels (putrescine, spermidine, and spermine) were determined in 24-hour urine samples by a high voltage electroporesis techique. Twenty-four of 26 patients with localized malignant tumors had two or more elevated urinary polyamine levels. Seven of 12 patients with regional spread of their cancer and five of 11 patients with localized benign and/or noninvasive tumors had elevated urinary polyamine levels. Elevations were seen more frequently frequently in patients with gynecologic tumors. Our data su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
1

Year Published

1977
1977
1985
1985

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 4 publications
0
5
1
Order By: Relevance
“…when she reported that patients with cancer excreted increased amounts of polyaniines in The potential clinical application of polyamines was suggested by Russell (197 1) urine. Since then, several investigators have reported elevated urinary polyamine levels among many patients with various solid tumors (Savory and Shipe, 1975;Bachrach, 1976), including patients with both localized and advanced disease (Lipton et al, 1975;Waalkes et al, 1975;Lipton et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…when she reported that patients with cancer excreted increased amounts of polyaniines in The potential clinical application of polyamines was suggested by Russell (197 1) urine. Since then, several investigators have reported elevated urinary polyamine levels among many patients with various solid tumors (Savory and Shipe, 1975;Bachrach, 1976), including patients with both localized and advanced disease (Lipton et al, 1975;Waalkes et al, 1975;Lipton et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…12 patients with head and neck cancer before and after either surgical or radiation therapy. the tumors were relatively small, the values in some were not above the normal range.…”
mentioning
confidence: 99%
“…Independent studies involving large numbers of patients showed that the levels of these amines were elevated in the urine of a majority of the cancer patients (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). One comprehensive study indicated that the potential usefulness of the urinary polyamines as biological markers was less promising than originally anticipated (13).…”
mentioning
confidence: 99%
“…In most previous studies, the biological samples (urine, serum, and cerebrospinal fluid) were hydrolyzed prior to analysis. The data presented (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) pertain to the quantities of total polyamines excreted in urine and not to the nature of these amines.…”
mentioning
confidence: 99%
See 1 more Smart Citation